The Multidimensional Nursing Generations Questionnaire: development, reliability, and validity assessments. (6th February 2017) - Stevanin, Simone; Bressan, Valentina; Vehviläinen‐Julkunen, Katri; Pagani, Laura; Poletti, Piera; Kvist, Tarja
Abstract : Purpose: To develop and perform reliability and validity assessments of the international Multidimensional Nursing Generations Questionnaire. Background: There are three generations of nurses in the European workforce. There is little research on the characteristics of these generations and the ways in which to manage them professionally, and no instrument has yet been developed to measure these aspects specifically. Methods: With results from previous studies, 69 nursing generations‐oriented items were created in English, translated into Italian and Finnish, and pretested to form the basis of an instrument that was tested between September and October 2014 on a sample of Finnish and Italian nurses ( n  = 1302) using principal component analysis and Cronbach's alpha. Results: Fifty‐four items and eight components (Cronbach's α range: 0.61–0.81) were identified in the instrument: (1) conflicts between generations; (2) patient safety view; (3) relationships between generations; (4) working as a multigenerational team; (5) orientation to change; (6) presenteeism and job propensity; (7) intention to leave, and (8) flexibility and availability. Conclusions: The instrument showed acceptable preliminary psychometric properties and satisfactory internal consistency. Implications for nursing management: The Multidimensional Nursing Generations Questionnaire is a useful tool to measure the characteristics of different generations of nurses and to develop management strategies tailored to those generations.